2019
DOI: 10.1021/acs.nanolett.9b00388
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Solar Energy Conversion: Biointerfaces for Artificial Photosynthesis and Biological Modulation

Abstract: Three seemingly distinct directions of nanomaterials research, photovoltaics, biofuel production, and biological modulation, have been sequentially developed over the past several decades. In this Mini Review, we discuss how the insights gleaned from nanomaterials-based solar energy conversion can be adapted to biointerface designs. Because of their size-and shape-dependent optical properties and excellent synthetic control, nanomaterials have shown unique technological advantages as the light absorbers or ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 105 publications
0
25
0
Order By: Relevance
“…278 At a subcellular scale, Au nanoclusters or molecular dyes have been exploited to intervene pathways within cells with light irradiation as bioorthogonal opportunities for intracellular modulation. 231,236,279 Furthermore, the intracellular metabolism can be coupled with extracellular redox transformations to manufacture functional materials such as polymers and inorganic particles. [280][281][282] These materials may provide additional benefits to promote extracellular electron transfer or cytoprotection.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…278 At a subcellular scale, Au nanoclusters or molecular dyes have been exploited to intervene pathways within cells with light irradiation as bioorthogonal opportunities for intracellular modulation. 231,236,279 Furthermore, the intracellular metabolism can be coupled with extracellular redox transformations to manufacture functional materials such as polymers and inorganic particles. [280][281][282] These materials may provide additional benefits to promote extracellular electron transfer or cytoprotection.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition to water molecules, there are many amino acid residues around the CaMn4O5 cluster 16,[32][33][34] . Water molecules and these amino acid residues are connected to the CaMn4O5 cluster by hydrogen bonds, which can not only stabilize the structure of the CaMn4O5 cluster, but also play an important role in OER process 35 . Bonded water molecules can provide initial reactants, facilitating rapid reactions 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Bonded water molecules can provide initial reactants, facilitating rapid reactions 36 . The surrounding amino acid residues facilitate the transfer of protons and electrons in the OER process and speed up the reaction rate 35 . Besides the four water molecules those are closely linked to the CaMn4O5 cluster, it has been found that there are more than 1300 water molecules in a single PSII monomer 37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] Therefore, improving the sunlight absorption efficiency of photosynthetic pigment is an efficient pathway to accelerate the growth and increase the production yield of crops. [ 3–5 ] To solve the problem, light conversion materials, which convert the useless sunlight into the blue–violet and red region, have attracted great attention in green agriculture recently. [ 6–8 ] Compared with the traditional methods such as chemical fertilizers and pesticides, using light conversion materials can reduce or even eliminate the detrimental pollution to the farmland soil and environment.…”
Section: Introductionmentioning
confidence: 99%